Rapra Collection of Infrared Spectra of Rubbers, Plastics, and Thermoplastic Elastomers - Sidwell, John (Rapra Technology Limited, 2011)
This collection is the result of a number of years work and provides a set of transmission and pyrolysate spectra of a comprehensive range of technically important rubber and plastic materials.